The development of cryo-EM into a mainstream structural biology technique - Nogales, Eva (Nat Methods, 2016)
Single-particle cryo-electron microscopy (cryo-EM) has emerged over the last two decades as a technique capable of studying challenging systems that otherwise defy structural characterization. Recent technical advances have resulted in a ‘quantum leap’ in applicability, throughput and achievable resolution that has gained this technique worldwide attention. Here I discuss some of the major historical landmarks in the development of the cryo-EM field, ultimately leading to its present success.